Electrophysiological measurements of holistic processing of Chinese characters - Qi, Zhengyang; Luo, Wenbo (Frontiers in Psychology, 2022)
Holistic processing is a marker of perceptual expertise in facial recognition. In the present study, we examined neural responses to the holistic processing of Chinese characters, adopting the composite paradigm. The behavioral results showed that the discrimination of congruent trials was significantly higher than that of incongruent trials, and participants responded faster. Moreover, the congruent trials elicited significantly larger N170 amplitude than the incongruent trials. The holistic processing effect of the N170 component was observed for upright characters, as the configural information of inverted characters and misaligned characters were destroyed. Right-lateralization of processing Chinese characters was observed in the N170 amplitudes and delta-theta band oscillations. The results suggested that Chinese character recognition employed a strategy of holistic processing, and the finding that neural indicators provide a better signal of the strength of holistic processing in Chinese characters than behavioral indicators was also crucial.